The Role of Geological Map for the Study of Mineral Reserves - Sattikhodjaevich, prof. Buzrukov Zakiryo (Antis Publisher, 2024)
The article deals with the method of creating a geological map in General, and specifically the creation of geological maps. In this regard, during the writing of the thesis was to analyze the state geological mapping to date, were digested subsequently creating a geological map exploration of ore deposits, were also fully justified methods for calculating mineral resources and the improvement of methods of creating geological maps of the ore deposit.